Paciente pediátrico con parálisis cerebral infantil y desnutrición grave basado en el modelo de marjory gordon - Gamarra Gualacio, Jhonatan Eduardo; Medina Medina, Diana Elizabeth (Machala : Universidad Técnica de Machala, 2020)
Introduction: Infant cerebral palsy is defined as a non-progressive, motorized brain injury that occurs before, during, or after birth. The overall prevalence of cerebral palsy is about 1.5 to 3 out of every 1,000 live newborns. In Ecuador, although there are no official statistics on the subject, the report of the National Council on Disabilities, reported 130,179 people with this disorder, divided into 110,000 cases for genetic congenital causes, and 20,000 for problems in childbirth, this being the nationally recognized figure. It is a chronic pathology that demands a long term care, such condition of the child generates a physical and mental wear in the primary caretaker, causing anxiety and depression influencing negatively in the strengthening of skills and abilities in the management of these cases. Objective: to determine the nursing care process in a patient diagnosed with infant cerebral palsy with severe malnutrition, based on Marjory Gordon's model. Methods: This research is scientific, analytical and descriptive. It was done by searching and analyzing scientific articles directed to the study, as well as reviewing and evaluating the clinical history and follow-up of the patient and her mother. Results: In relation to other works, it can be evidenced that patients with infantile cerebral palsy in its complications have malnutrition due to bad swallowing and handling of food, as well as respiratory problems, since most of them are exposed due to paralysis.
Introducción: La parálisis cerebral infantil se define como una lesión no progresiva y motriz del cerebro, la cual ocurre antes, durante o después del parto. La prevalencia global de parálisis cerebral se sitúa alrededor de un 1,5 a 3 de cada 1.000 recién nacidos vivos. En Ecuador, aunque no existen estadísticas oficiales sobre el tema, el informe del Consejo Nacional de Discapacidades, reportó 130.179 personas con este trastorno, repartidos de 110 mil casos por causas congénitas genéticas, y 20 mil por problemas en el parto, siendo esta la cifra reconocida a nivel nacional. Es una patología crónica que exige un cuidado a largo plazo, dicha condición del niño genera un desgaste físico y mental en el cuidador primario, ocasionando ansiedad y depresión influyendo negativamente en el fortalecimiento de habilidades y destrezas en el manejo de estos casos. Objetivo: determinar el proceso de atención de enfermería en un paciente con diagnóstico de parálisis cerebral infantil con desnutrición grave, basado en el modelo de Marjory Gordon. Métodos: Esta investigación es de tipo científico, analítico y descriptivo, se la realizó mediante búsqueda y análisis de artículos científicos direccionados al estudio, así como revisión y valoración de la historia clínica y seguimiento de la paciente y su madre.
Keywords: PARALISIS CEREBRAL INFANTIL; DESNUTRICION; PROCESO DE ATENCION DE ENFERMERIA